1975
DOI: 10.1159/000251348
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Immunological Status of Patients with Dermatophytoses

Abstract: 22 patients with Trichophyton rubrum infection were studied for some of their immunological parameters. The trichophytin skin test performed with commercially available Dermatophytin (Hollister-Stier) gave immediate positive reaction in 3 patients. All the other patients gave negative delayed and retarded reactions. In vitro response to PHA of the peripheral lymphocytes was significantly depressed in patients as compared to the controls. No relationship could, however, be established between the severity, dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The proportion of cross reactions is similar to that obtained by other authors (12,19,20,21), indicating the existence of common components in the antigenic substances which do not enable us to diagnose a species response but do enable us to diagnose a group response, i. e., whether there exists, or has existed, an infection by dermatophytes.…”
Section: Discussionsupporting
confidence: 82%
“…The proportion of cross reactions is similar to that obtained by other authors (12,19,20,21), indicating the existence of common components in the antigenic substances which do not enable us to diagnose a species response but do enable us to diagnose a group response, i. e., whether there exists, or has existed, an infection by dermatophytes.…”
Section: Discussionsupporting
confidence: 82%
“…However, they did find a general depression of lymphocyte responses to mitogens and nondermatophyte antigens in a few patients with chronic infections due to T. mentagrophytes. Abraham et al (1975) also found evidence of a general depression of T-Iymphocyte reactivity in patients with T. rubrum who had no delayed-type cutaneous reactions to "trichophytin. "…”
mentioning
confidence: 87%
“…Their defective cell-mediated immune response therefore does not appear to reflect a primary immunodeficiency (Fudenberg et at., 1971;Bean and South, 1973). However, depressed T-cell reactivity to phytohemagglutinnin has also been reported in patients with chronic T. rubrum (Abraham et at., 1975).…”
Section: Infection In Susceptible Hostsmentioning
confidence: 99%
See 2 more Smart Citations